Permeation properties of chitosan-nanofiller membranes - Soh, Yi Lin. (2010)
With the organic-inorganic hybrid membranes receiving considerable attentions due to the combination of the process ability of the organic polymer phase with superior transport property of the inorganic phase, chitosan-zeolite membranes were fabricated. The loading of the nanofillers are 0wt.%, 1wt.%, 5wt.% and 9wt.%. These membranes were characterized using the Scanning Electron Microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). The effects of the nanofiller loadings on the water vapor permeability were evaluated. The diffusion coefficients at different loadings were also estimated. Generally, the addition of hydrophilic MCM-41 particles resulted in increased diffusion coefficient and permeability. However, the properties remain relatively stable with increased MCM-41 loadings. For hydrophobic ZSM-5, the diffusion coefficient and permeability dropped when 1% of ZSM-5 is added and the diffusion coefficient only increased higher than pure chitosan membrane at 5% loading. With increased loadings of ZSM-5 from 1% to 9%, the diffusion coefficients and permeability increased. The optimal permeability between the 2 zeolite hybrid membranes is evaluated to be at 9% CS/MCM-41 membrane. Lastly, an additional test for chitosan/clay hybrid membrane was carried out. With the addition of clay, both diffusion coefficient and permeability increased. With increased loadings of Clay from 1% to 9%, the diffusion coefficients and permeability decreased.